THE ANTIBACTERIAL ACTIVITY OF GLYCOLIPOPEPTIDE PRODUCED FROM LACTOCOCCUS LACTIS HN21 AGAINST SOME CLINICAL PATHOGENS IN COMBINED WITH SOME STANDARD ANTIBIOTICS - Hala. M. A,; N. H. Haider, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to produce a biosurfactant from Lactococcus sp. and study its synergistic effects with some standard antibiotics. Lactococcus sp. HN21 isolate was selected for its highly biosurfactant production and antibacterial activity. It was identified by 16s r RNA as Lactococcus lactis HN21. Optimum conditions for production were studied and it was: Modified M17 media (M17 media with some modifications in its composition) at ph 6.5, for 96 hrs incubation time. The E24% at these conditions was 77%. FTIR and GC-MS results identified the produced biosurfactant as glycolipopeptide with a major fatty acid octadecenoic acid. P. aeruginosa was successfully inhibited by the glycolipopeptide alone, with overall inhibition ranging from (15 to 19 mm). The combined use of antibiotics and glycolipopeptide, however, resulted in an increase in the total inhibition zones to (17 to 28 mm), while glycolipopeptide alone was effective against S. aureus and showed total inhibition zones ranging from (15 to 22) mm.  glycolipopeptide in combination with antibiotics, the total inhibition zones were increased (26 to 40) mm. The results observed a great pharmaceutical application in increasing the bactericidal effect.